THE ROLE OF TOURISM AND CULTURE DEPARTMENT OF SIKKA DISTRICT AND VILLAGE GOVERNMENT IN THE DEVELOPMENT OF THE TOURISM SECTOR OF KOLISIA B VILLAGE - Maria Frebiyati; Danar Aswim (Journal Civics And Social Studies, 2022)
This study aims to determine the extent of the Role of the Tourism and Culture Office of Sikka Regency and the Village Government in the Development of the Tourism Sektor in Kolisia B Village and what are the inhibiting factors in the development of the tourism sektor. This study uses a descriptive qualitative approach. The data sources used are primary data sources and secondary data sources. The informants involved in this study were the Department of Tourism and Culture in the section on developing tourist attractions and the Village Government of Kolisia B. The data collection techniques used were observation, interview and documentation techniques. Data analysis techniques include data reduction (data reduction), data display (data presentation) and conclusion drawing/verification. Based on the results of the study, the role of the Sikka Regency Tourism and Culture Office and the Village Government have carried out their role by providing training activities to the community, providing facilities in the form of rest areas for visitors, seats and public toilets, and establishing partnerships with private parties such as the NTT BANK, then The Department of Tourism and Culture and the Village Government have carried out their roles quite effectively to meet the needs and problems in the development of the tourism sektor, there are also various inhibiting factors in the development of the tourism sektor in the form of budgets, human resources, land ownership status and promotional media. The Sikka Regency Tourism and Culture Office and the Village Government need to socialize the community in stages to increase community participation in the development of the tourism sektor. There needs to be innovation and creativity in promoting tourism in print or internet media, so that tourism objects can be recognized, and there needs to be new breakthroughs made by the Tourism and Culture Office and the Village Government so that visitors are interested in visiting tourist attractions.